In situ Synthesis of Supramolecular Polymers: Finding the Right Conditions when Combining Covalent and Non‐Covalent Synthesis. Issue 34 (14th July 2022) - Schnitzer, Tobias; Jansen, S. A. H.; Mabesoone, Mathijs F. J.; Vantomme, Ghislaine; Meijer, E. W.
Abstract: The combination of covalent and non‐covalent synthesis is omnipresent in nature and potentially enables access to new materials. Yet, the fundamental principles that govern such a synthesis are barely understood. Here, we demonstrate how even simple reaction mixtures behave surprisingly complex when covalent reactions are coupled to self‐assembly processes. Specifically, we study the reaction behavior of a system in which the in situ formation of discotic benzene‐1, 3, 5‐tricarboxamide (BTA) monomers is linked to an intertwined non‐covalent reaction network including self‐assembly into helical BTA polymers. This system shows an unexpected phase‐separation behavior in which an interplay of reactant/product concentrations, side‐products and solvent purity determines the system composition. We envision that these insights can bring us one step closer to how to design the synthesis of systems in a combined covalent/non‐covalent fashion. Abstract : A combination of covalent and non‐covalent synthesis steps is promising to construct synthetic supramolecular systems. Yet, the fundamental principles that guide such an approach are barely understood. Here, the reaction behavior of in situ formed supramolecular polymers is studied, in which covalent reactions are intertwined with a non‐covalent reaction network leading to an unexpected phase‐separation behavior that determines the system composition.